An Investigation of Science Learning Difficulties Among Deaf Students in Inclusive Elementary Schools - Made Wimas damayanti; Putu Nanci Riastini; Dewa Gede Firstia wirabrata (MIMBAR PGSD Undiksha, 2026)
Deaf students face various difficulties in learning science, especially in understanding and remembering scientific terms, understanding abstract concepts, and receiving information verbally. The learning received still uses the lecture method without curriculum adjustments, with media limited to textbooks, pictures, LKPD, and videos from the internet That are not specifically designed. This study aims to describe learning difficulties and the factors that cause them in deaf students in science learning. The approach used is descriptive qualitative with interview, observation, and documentation techniques, and data analysis using triangulation. The results of the study indicate that the factors causing learning difficulties include monotonous learning methods, lack of appropriate learning media, low motivation to learn, differences in individual characteristics, limited parental support, lack of vocabulary or sign language equivalents for science terms, lack of inclusive learning planning, and no differentiated learning. This study provides an important picture of the obstacles experienced by deaf students in science learning and becomes the basis for developing more inclusive and effective learning strategies.